PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN ALAMDENGAN PENERAPAN METODE DEMONSTRASISISWA KELAS V SD NEGERI 014 BERINGIN MAKMURKECAMATAN KERUMUTAN - Kamril (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The background of this study was the low science (IPA) learning outcomes of students at SDN 014 Beringin Makmur, where out of 25 students only 12 students (48%) achieved the minimum mastery criterion (KKM). This classroom action research (PTK) was conducted by applying the demonstration method and was carried out in two cycles. The study focused on improving students’ science learning outcomes. The results showed that students’ science learning outcomes increased in each cycle. In the preliminary data, the average science learning outcome score was 65 with a mastery percentage of 50%. In the first cycle, the average science learning outcome increased to 69.25 with a mastery percentage of 67%, and in the second cycle it further increased to an average score of 74.5 with a mastery percentage of 85%.